2017
DOI: 10.1093/abbs/gmx040
|View full text |Cite
|
Sign up to set email alerts
|

CXCL16 deficiency attenuates acetaminophen-induced hepatotoxicity through decreasing hepatic oxidative stress and inflammation in mice

Abstract: Chemokine C-X-C ligand 16 (CXCL16), a single-pass Type I membrane protein belonging to the CXC chemokine family, is related to the inflammatory response in liver injury. In present study, we investigated the pathophysiological role of CXCL16, a unique membrane-bound chemokine, in acetaminophen (APAP)-induced hepatotoxicity in mice. Mice were injected with APAP, and blood and tissue samples were harvested at different time points. The serum high-mobility group box 1 and CXCL16 levels were quantified by sandwich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…neutrophil accumulation [41] . These studies, in accordance with our findings, suggest that the inhibition of the CXCL16 pathway alleviates renal tubular interstitial injury by suppressing inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…neutrophil accumulation [41] . These studies, in accordance with our findings, suggest that the inhibition of the CXCL16 pathway alleviates renal tubular interstitial injury by suppressing inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly the best studied role for SR-PSOX in the recruitment of leukocytes is in the context of hepatic inflammation (207), with its endothelial-expressed form known to interact with intrahepatic CXCR6 + immune cells, such as effector T cells (206, 208), natural killer (NK) cells (209, 210) and NKT cells (199). It has recently been shown that genetic deficiency of SR-PSOX in mice inhibits the extent of inflammation in a model of acetaminophen (APAP)-induced acute liver injury (211). In addition, pharmacological intervention with neutralizing antibodies raised against SR-PSOX has shown inflammation-reducing efficacy in preclinical murine models of sepsis-mediated (212, 213) and carbon tetrachloride (CCl 4 )-mediated (207) acute liver injury.…”
Section: Scavenger Receptors In Leukocyte Traffickingmentioning
confidence: 99%
“…81 Several preclinical studies targeting VAP-1 have confirmed that inhibition of its enzymatic activity and/or blockade of its adhesive function with therapeutic antibodies reduces leukocyte infiltration in a range of rodent models of inflammatory diseases. 82 Scavenger receptor that binds phosphatidylserine and oxidized lipids (SR-PSOX), which in its soluble form is also known as the chemokine, CXCL16, is expressed by LSEC 35 and is upregulated in both acutely 83,84 and chronically injured liver tissues. 85 CXCL16 is a specific ligand for the chemokine receptor CXCR6, thus enabling its membrane-bound form to interact with intrahepatic CXCR6 Ăž immune cells, such as effector T cells, 85,86 natural killer (NK) cells, 87,88 and NKT cells.…”
Section: Atypical Adhesion Moleculesmentioning
confidence: 99%
“…35 Genetic deficiency of SR-PSOX has recently been shown to reduce the extent of inflammation and necrosis in a murine model of acetaminophen (APAP)-induced acute liver injury. 83 Additionally, and perhaps more encouragingly, pharmacological intervention with neutralizing antibodies against SR-PSOX has shown efficacy in reducing inflammation in preclinical murine models of sepsis-mediated 84,89 and carbon tetrachloride (CCl 4 )-mediated 90 acute liver injury. Furthermore, Wehr and colleagues were also able to demonstrate the efficacy of SR-PSOX antibody therapy in a commonly used murine model of NASH, showing a reduction in both macrophage infiltration and triglyceride levels.…”
Section: Atypical Adhesion Moleculesmentioning
confidence: 99%